2023
DOI: 10.3390/ani13071233
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Abnormalities on Thoracic Radiographs of Dogs and Cats

Abstract: Evaluation of the sternum is part of the routine examination of small animal thoracic radiographs. However, descriptions on frequency and type of abnormalities are lacking. This retrospective observational study aimed to describe abnormal radiographic findings of the sternum in a cross-section of client-owned dogs and cats undergoing thoracic radiography between 1 January 2019 and 1 January 2021 for reasons unrelated to diseases of the sternum. The study population consisted of 777 dogs (mean age, 7.3 ± 3.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In all cats described in the literature, a traumatic origin is suspected as in the case of our patient. In the study of Van den Broek et al [ 1 ], marked degenerative changes of the intersternebral joints were observed in 5 dogs just at the level of sternal subluxation. It might suggest spontaneous dislocation possible following subclinical instability and arthropathy of these joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cats described in the literature, a traumatic origin is suspected as in the case of our patient. In the study of Van den Broek et al [ 1 ], marked degenerative changes of the intersternebral joints were observed in 5 dogs just at the level of sternal subluxation. It might suggest spontaneous dislocation possible following subclinical instability and arthropathy of these joints.…”
Section: Discussionmentioning
confidence: 99%
“…The sternum plays a major role by protecting the heart and lungs and aids in breathing motion [ 1 ]. Sternal luxation/dislocation is a rare condition and is most often the result of trauma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%